Implementasi Generative AI dalam Mendukung Keterampilan Menulis Akademik Mahasiswa - Elsa Arifatul Fauziah; Surana Surana (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
The rapid development of Generative Artificial Intelligence (AI) technology has brought about significant changes in various fields, including higher education. One of its primary functions is to assist students in completing academic writing assignments. This study aims to explore the use of Generative AI in enhancing students’ academic writing skills and to identify the advantages and challenges faced in the field of education. The method used in this study is a literature review, analyzing various scientific works from both domestic and international sources regarding Generative AI, scientific writing, and higher education published between 2023 and 2025. The findings indicate that Generative AI can assist students in formulating ideas, structuring their writing, improving grammar, and boosting writing productivity. Additionally, this technology contributes to enhancing students’ confidence and efficiency in the academic writing process. However, various challenges were also identified, such as the risk of academic misconduct, excessive reliance on AI-generated content, and concerns regarding the accuracy and authenticity of information. Therefore, the use of generative AI must be accompanied by digital literacy and an understanding of ethical considerations to ensure its responsible use in educational settings. This study indicates that generative AI has great potential to improve academic writing skills when used appropriately and responsibly.